A Patient-Centered Approach to Communication during Endoscopic Procedures: The Importance of Providing Information to Patients - Osnat Bashkin; Rita Boltean; Revaya Ben-Lulu; Mor Aharon; Ruhama Elhayany; Avraham Yitzhak; Revital Guterman; Naim Abu-Freha (MDPI AG, 2024)
The study aimed to explore patients' experiences and perceptions throughout the various stages of endoscopic procedures and examine the association between patient-centered communication and the patient's experience. A total of 191 patients responded to pre- and post-procedure surveys that inquired about fear and pain, patients' satisfaction regarding the information provided to them, perceptions and experience. Pain was associated with post-procedure fear (r = 0.63, p < 0.01) and negatively associated with reported patient experience at the end of the visit (r = −0.17, p < 0.01). Significant positive associations were found between patient experience and satisfaction from the information provided before (r = 0.47, p < 0.01) and the information provided after the procedure (r = 0.51, p < 0.001). A predictive model found that perceptions toward the physicians, satisfaction from information provided before discharge, and feelings of trust are predictors of the patient experience (F = 44.9, R2 = 0.61, p < 0.001). Patients' satisfaction with information provided before and after the procedure can positively affect the patients' experience, leading to a decrease in fear and anxiety and increasing compliance with medical recommendations. Strategies for PCC with endoscopic patients should be developed and designed in a participatory manner, taking into account the various aspects associated with the patient experience.